081 Ultrasound-guided muscle biopsy: a practical alternative for investigation of myopathy. Issue 6 (27th May 2022) - Ashraghi, Mohammad; Raithatha, Anish; Lord, Christopher; Limback-Stanic, Clara; Viegas, Stuart; Amiras, Dimitri
Abstract : Objective: We propose the use of ultrasound-guided muscle biopsy as a viable method of obtaining muscle specimen to aid the diagnosis of myopathy. We retrospectively review the diagnostic accuracy and patient feedback of ultrasound-guided muscle biopsies in our neuromuscular service. Method: Mul- tidisciplinary team meeting reviewed select patients and agreed on those suitable for ultrasound-guided muscle biopsy. They underwent biopsy using direct ultrasound guidance and a modified Bergström needle. The specimens were sent for histopathological analysis and patients were given a feedback form. Results: 10 patients underwent 11 ultrasound-guided muscle biopsies. Of these 11, 1 was processed incorrectly, but all others were suitable for analysis. All of those processed correctly aided diagnosis. All patient feedback was rated good or excellent. In 4 patients with a previous unsuccessful surgical biopsy, ultrasound-guided biopsy was successful in obtaining suitable muscle. Of those 4 patients, 2 preferred ultrasound-guided biopsy and 2 did not state a preference. Discussion: Our ultrasound-guided muscle biopsy technique offers an alternative to surgical biopsy. It yields high quality specimens that aids diagnosis and receives good patient feedback. It can be performed as a day-case and does not require theatre space. Fur- thermore, direct visualization of structures minimizes complications and allows biopsy of otherwise difficult targets. Conclusion: Utilisation of ultrasound-guided modified Bergström needle technique for muscle biopsy provides comparable success rates to other techniques, and has several benefits compared to alternative techniques. m.ashraghi@nhs.net